Microalgae wastewater treatment: Biological and technological approaches. Issue 12 (7th November 2019) - Wollmann, Felix; Dietze, Stefan; Ackermann, Jörg‐Uwe; Bley, Thomas; Walther, Thomas; Steingroewer, Juliane; Krujatz, Felix
Abstract: Current global environmental issues raise unavoidable challenges for our use of natural resources. Supplying the human population with clean water is becoming a global problem. Numerous organic and inorganic impurities in municipal, industrial, and agricultural waters, ranging from microplastics to high nutrient loads and heavy metals, endanger our nutrition and health. The development of efficient wastewater treatment technologies and circular economic approaches is thus becoming increasingly important. The biomass production of microalgae using industrial wastewater offers the possibility of recycling industrial residues to create new sources of raw materials for energy and material use. This review discusses algae‐based wastewater treatment technologies with a special focus on industrial wastewater sources, the potential of non‐conventional extremophilic (thermophilic, acidophilic, and psychrophilic) microalgae, and industrial algae‐wastewater treatment concepts that have already been put into practice.